Echo-endoscopic drainage of retrogastric pancreatic pseudocysts as a bridge-to-surgery for complicated cases of duodenal duplication cyst: case report - Pacifique, Joseph Xavier; Jauquier, Nicolas; Divjak, Natalie; Godat, Sebastien; Vasseur Maurer, Sabine (Frontiers in Pediatrics, 2025)
IntroductionDuodenal duplication cysts (DDC) are rare congenital malformations which are generally diagnosed in the first decade of life. The clinical presentation of DDC is highly variable and may be complicated by pancreatitis. When pancreatic pseudocysts (PPC) develop, definitive DDC treatment is delayed and exposes the patient to recurrent episodes of pancreatitis which further lengthen the process. We present a novel approach to the management of such cases by using echo-endoscopic cystogastric drainage of a large retrogastric PPC as a bridge to surgery. To our knowledge, this is the youngest reported case.CaseA 21-month-old girl presented with abdominal pain, bloating, vomiting and failure to thrive lasting for 3 months. Her prior medical history was normal.Diagnosis, therapeutic intervention and outcomesBlood work showed pancreatitis. Ultrasound (US) showed multiple cysts inside the abdomen. A thoraco-abdominal magnetic resonance imaging (MRI) scan allowed differentiation between multiple PPC and a DDC, which had caused a complicated obstructive pancreatitis. The DDC was confirmed by biopsies. Further imaging identified a large persistent retrogastric pseudocyst. Due to poor feeding and stable but compromised general condition, a two-step procedure was scheduled with echo-endoscopic cystogastric drainage of the large retrogastric PPC to reduce the convalescence time after the last episode of pancreatitis, followed by surgical resection of the DDC. The patient was released from the hospital the day after this procedure as oral intake had normalized. Unfortunately, 3 weeks after this procedure, the patient developed a septic shock due to infection of the remaining cysts. As surgery was required to treat the sepsis, the DDC was resected at the same time.ConclusionEcho-endoscopic cystogastric drainage is feasible and effective in children as young as 21 months. Pediatric guidelines have yet to be determined for this procedure.